(4x+3)(3x-4)=0

Simple and best practice solution for (4x+3)(3x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+3)(3x-4)=0 equation:


Simplifying
(4x + 3)(3x + -4) = 0

Reorder the terms:
(3 + 4x)(3x + -4) = 0

Reorder the terms:
(3 + 4x)(-4 + 3x) = 0

Multiply (3 + 4x) * (-4 + 3x)
(3(-4 + 3x) + 4x * (-4 + 3x)) = 0
((-4 * 3 + 3x * 3) + 4x * (-4 + 3x)) = 0
((-12 + 9x) + 4x * (-4 + 3x)) = 0
(-12 + 9x + (-4 * 4x + 3x * 4x)) = 0
(-12 + 9x + (-16x + 12x2)) = 0

Combine like terms: 9x + -16x = -7x
(-12 + -7x + 12x2) = 0

Solving
-12 + -7x + 12x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -4x)(4 + -3x) = 0

Subproblem 1

Set the factor '(-3 + -4x)' equal to zero and attempt to solve: Simplifying -3 + -4x = 0 Solving -3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = 0 + 3 -4x = 0 + 3 Combine like terms: 0 + 3 = 3 -4x = 3 Divide each side by '-4'. x = -0.75 Simplifying x = -0.75

Subproblem 2

Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333

Solution

x = {-0.75, 1.333333333}

See similar equations:

| yb+ax=c | | Y-2=(-2-3) | | 1.32(x+y)=32 | | Y-2=(-3-3) | | 12=6x-8x | | 284.7+14.6= | | -14.4=-0.6 | | 3(x*31)=31.3 | | 3s-6=5 | | -7k-9=1 | | 3x+-8y+4=11 | | 7x+4=-6x-22 | | 6(d+7)-20=6x | | 0.66+4=-0.33x-4 | | 3(10)=2y+6 | | 24+8k=9 | | 3(8)=2y+6 | | y(2-y)=6-(y(y)+3y-4) | | 3(4)=2y+6 | | 4y=-6x+8 | | (x+7)2-(x+(-2))(x+(-1))=0 | | 7x-11=5(x-2)+2x-1 | | x-2=-4y | | -6=k+1-8k | | 48x-37y= | | 3(0)=2y+6 | | 2+y=8+4 | | 3(-2)=2y+6 | | 8=-5x-3x | | y=-7+7 | | 15d+25=15d+25 | | 3(6y-3)-(7y-8)= |

Equations solver categories